Further evidence on the link between finance and growth: an international analysis of community banking and economic performance - Allen N. Berger; Iftekhar Hasan; Leora F. Klapper (Bank of Finland, 2004)
We seek to contribute to both the finance-growth literature and the community banking literature by testing the effects of the relative health of community banks on economic growth and investigating potential transmission mechanisms for these effects using data from 1993- 2000 on 49 nations.Data from both developed and developing nations suggest that larger market shares and higher efficiency rankings for small, private, domestically owned banks are associated with better economic performance, and that the marginal benefits of larger shares are greater when the banks are more efficient.Only mixed support is found for hypothesized transmission mechanisms through improved financing for SMEs or greater overall bank credit flows.The data from developing nations is also consistent with favourable economic effects from foreign-owned banks, but unfavourable effects from state-owned banks.
URN:NBN:fi:bof-20140807330
Keywords: G21; G28; G34; F36; 330; banks; community banking; SMEs; financial development; economic growth; international